Endosaccular flow disruption: where are we now?. (13th June 2019) - Bhogal, Pervinder; Udani, Sundip; Cognard, Christophe; Piotin, Michel; Brouwer, Patrick; Sourour, Nader-Antoine; Andersson, Tommy; Makalanda, Levansri; Wong, Ken; Fiorella, David; Arthur, Adam S; Yeo, Leonard LL; et al.
Abstract : Endosaccular flow disruption is an innovative method of treating wide-necked complex aneurysms. Currently four types of devices have obtained the CE mark for use within Europe. These are the Woven EndoBridge device (WEB), the Luna Aneurysm Embolization System, the Medina Embolic Device (Medtronic), and the Contour Neurovascular System. The aim of this article is to provide an overview of these devices and to summarize the evidence in the literature pertaining to the treatment of intracranial aneurysms with them.